Alizarin Red–Tb3+ complex as a ratiometric colorimetric and fluorescent dual probe for the smartphone-based detection of an anthrax biomarker. Issue 33 (6th August 2019) - Xu, Miao; Huang, Wei; Lu, Dingkun; Huang, Chunyu; Deng, Jingjing; Zhou, Tianshu
Abstract : A ratiometric colorimetric and fluorescent dual probe was developed for the smartphone-based detection of DPA from bacterial spores. Abstract : In this work, a novel dual-sensing probe was developed for detecting an anthrax biomarker (dipicolinic acid, DPA) based on the competitive coordination of Tb 3+ between DPA and Alizarin Red (AR). UV-vis titration experiments demonstrated that AR and Tb 3+ ions formed a 3 : 1 coordination pair in a boric acid–borate buffer solution. However, the subsequent addition of DPA to the complex solution destroyed the coordination of AR–Tb 3+ completely, resulting in the formation of DPA–Tb 3+ . This constructed a new mechanism of ratiometric colorimetric and fluorescence dual-mode sensing for DPA. By integrating a smartphone with an easy-to-access color-scanning APP, this dual-sensing method could be further applied as a reliable scanometric assay for the rapid and on-site visible detection of DPA directly. With the method established by us, the sensitive and selective detection of DPA released from bacterial spores could be realized easily.